2017
DOI: 10.1038/cr.2017.79
|View full text |Cite
|
Sign up to set email alerts
|

Alternate binding modes of anti-CRISPR viral suppressors AcrF1/2 to Csy surveillance complex revealed by cryo-EM structures

Abstract: Bacteriophages encode anti-CRISPR suppressors to counteract the CRISPR/Cas immunity of their bacterial hosts, thus facilitating their survival and replication. Previous studies have shown that two phage-encoded anti-CRISPR proteins, AcrF1 and AcrF2, suppress the type I-F CRISPR/Cas system of Pseudomonas aeruginosa by preventing target DNA recognition by the Csy surveillance complex, but the precise underlying mechanism was unknown. Here we present the structure of AcrF1/2 bound to the Csy complex determined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
59
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 46 publications
4
59
0
Order By: Relevance
“…As expected, the general arrangement of the 9 polypeptides in the Csy crRNA ·dsDNA is the same as that reported in the cryo-EM structure of Csy crRNA bound simultaneously to inhibitors AcrF1 and AcrF2 by Chowdhury et al (2017) and by Peng et al (2017), with the protein subunits arranged around the crRNA in a helically twisted “G” shape (Figure 1C, 1D). Cas6f is located at the 3′ stem-loop of the crRNA, Cas8f and Cas5f are located at the 5′ handle of crRNA, and six interlocking copies of Cas7f are located along the length of the crRNA spacer.…”
Section: Resultssupporting
confidence: 82%
“…As expected, the general arrangement of the 9 polypeptides in the Csy crRNA ·dsDNA is the same as that reported in the cryo-EM structure of Csy crRNA bound simultaneously to inhibitors AcrF1 and AcrF2 by Chowdhury et al (2017) and by Peng et al (2017), with the protein subunits arranged around the crRNA in a helically twisted “G” shape (Figure 1C, 1D). Cas6f is located at the 3′ stem-loop of the crRNA, Cas8f and Cas5f are located at the 5′ handle of crRNA, and six interlocking copies of Cas7f are located along the length of the crRNA spacer.…”
Section: Resultssupporting
confidence: 82%
“…XaCsy1 and XaCsy2 form a stable heterodimeric complex-It has previously been shown in P. aeruginosa that Csy1 and Csy2 form a heterodimeric subunit, which is localized at the periphery of the Csy complex (22,24,25,36,38,47). The interaction between Csy1 and Csy2 was also detected in Pectobacterium atrosepticum (23).…”
Section: Resultsmentioning
confidence: 85%
“…Previous cryo-EM structures for the AcrF2-bound P. aeruginosa Csy complex have been determined to moderate resolutions (25,38,47). One study reported that the average resolution was 3.4 Å, and the authors stated that the density of acidic residues on AcrF2 was not sufficient to confidently model side chain positions (25).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations